Application of the MACRO Model Approach to the Interpretation Management of Creative Tourism in the form of Coffee in Khao Kho Sub-district Phetchabun Province - Kaeowiset, Thitikarn (Community and Social Development Journal, 2023)
The goal of this study was to spread information about interpretative management of creative coffee tourism using the MACRO model approach and to create new strategies for promoting coffee-based creative tourism in Khao Kho Subdistrict, Khao Kho District, and Phetchabun Province. The 40 people who are interested in taking part in the project of utilizing the MACRO model approach to transmit Khao Kho Arabica Coffee tour guides from beginning to finish and the 40 people who are coffee growers in the Khao Kho Sub-district of Phetchabun Province are the target demographics. The tools used in this research are; 1) a creative guide utilizing the MACRO model method to promote coffee-based community creative tourism, and 2)interpretative activities and a guidebook for tourism from source to mouth Using the MACRO model approach, Khao Kho Arabica coffee is a form used to interview project participants. The results showed that utilizing MACRO model approach with an IOC value of 0.89, guidelines and interpretative activities for tourism from source to mouth, Khao Kho Arabica coffee goods, which are values that may be used, and the final product after that, the researcher has improved and then communicated to the group of coffee producers and interested parties the guidebook and interpretative tourist activities from the beginning to the mouth, Khao Kho Arabica coffee goods. According to the transfer findings, participants in the project were highly satisfied with their engagement in the project of transferring the handbook and interpreting tourism activities, with an average of 4.66 and a standard deviation of 0.47. Participating in the activity encourages participants to construct a learning process through group brainstorming to create a body of information they can use to advance their careers and share with the general public.